One good thing - Hunter, Georgia, 1978- (Pamela Dorman Books/Viking, 2025)
"From the New York Times-bestselling author of We Were the Lucky Ones, an unforgettable story of hardship and hope, courage and resilience, that follows one young woman's journey through war-torn Italy 1941, Emilia Romagna. Lili and Esti have been best friends since meeting at the University of Ferrara; when Esti's son Theo is born, they become as close as sisters. There is a war being fought across borders, and in Italy, Mussolini's Racial Laws have deemed Lili and Esti descendants of an 'inferior' Jewish race, but life somehow goes on--until Germany invades northern Italy, and the friends find themselves in occupied territory. Esti, older and fiercely self-assured, convinces Lili to flee first to a villa in the countryside to help hide a group of young war orphans, then to a convent in Florence, where they pose as nuns and forge false identification papers for the Underground. When disaster strikes at the convent, a critically wounded Esti asks Lili to take a much bigger step: To go on the run with Theo. Protect him while Esti can't. Terrified to travel on her own, Lili sets out on an epic journey south toward Allied territory, through Nazi-occupied villages and bombed-out cities, doing everything she can to keep Theo safe. A remarkable tale of friendship, motherhood, and survival, One Good Thing is a tender reminder that love for another person, even amidst darkness and uncertainty, can be reason to keep going"--